2018
DOI: 10.1590/0034-7167-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the defining characteristics in nursing diagnoses of Hyperthermia in newborns

Abstract: four characteristics of high specificity contribute to Hyperthemia. However, stupor is the only one with significant sensitivity to identify it at its early-stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…It is perceived, by having the limited capacity to sweat, that the infant may become irritated and agitated or assume an extended, flaccid position, to increase the heat transfer to the environment from the skin. 12 It is verified, in relation to the ND risk of infection, that the article under study understands that there is an inadequate acquired immunity in the NB. It is understood that neonatal infections represent a major problem that depends on measures that apply to the pregnant woman, to the hospital environment, to the care team and to the NB itself.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is perceived, by having the limited capacity to sweat, that the infant may become irritated and agitated or assume an extended, flaccid position, to increase the heat transfer to the environment from the skin. 12 It is verified, in relation to the ND risk of infection, that the article under study understands that there is an inadequate acquired immunity in the NB. It is understood that neonatal infections represent a major problem that depends on measures that apply to the pregnant woman, to the hospital environment, to the care team and to the NB itself.…”
Section: Discussionmentioning
confidence: 93%
“…In this sense, it should be noted that the rectal temperature will be warmer than the skin temperature. 12 On the other hand, in the infant, hyperthermia caused by exposure to an overheated environment causes the NB to gain heat through convection. It is described, first, that there will be an increase in the skin temperature, then the central temperature, followed by vasodilatation and cardiac and respiratory overloads.…”
Section: Discussionmentioning
confidence: 99%
“…11 There was a strong correlation between axillary with rectal temperature. 12,13 By tradition, the axillary temperature is adjusted to rectal temperature by adding 0.5 C. 7 Since the body temperature of the infant depends mainly on environmental temperature, 14,15 during treatment with phototherapy, an increase in environmental temperature subsequently increases the risk of hyperthermia. During 24 h of treatment, the study showed that axillary temperature, rectal temperature, and crib temperature were higher in no filter film groups.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies used the accuracy method [7][8][9][10][11][12][13][14][15] for clinical validation of the studied phenomena. Of these, six (35.29%) used the latent classes analysis as a statistical approach [7][8][9][10][11][12] and the other three (17.64%) used the accuracy measures. [13][14][15] Accuracy represents the ability of a given test to correctly point out whether or not an individual has the disease.…”
Section: Discussionmentioning
confidence: 99%